Error Patterns and Predictors in Solving Algebraic Word Problems: Evidence from Secondary School Students - Emmanuel Gyimah Osei; Frederick Adu Gardiner; Johnson Dzotsi (EDUPEDIA PUBLISHER, 2026)
Purpose: Mathematics word problems, particularly in linear equations, remain challenging for secondary students due to difficulties in comprehension and algebraic reasoning. This study aims to analyze students’ errors in solving linear equation word problems using Newman’s Error Analysis, identify the underlying causes, and examine instructional practices that influence students’ performance. Methodology: A descriptive mixed-methods approach was employed, combining 220 students’ written responses to word problem tasks with 10 teacher interviews. Quantitative data were analyzed using descriptive statistics to determine the distribution of error types, while qualitative data were examined through thematic analysis to explore students’ difficulties and instructional factors. Findings: The findings indicate that errors occurred across all stages of Newman’s framework, with comprehension, transformation, and encoding errors being the most dominant, while reading errors were relatively minimal. Students experienced difficulties in interpreting problem contexts, translating verbal statements into algebraic expressions, and presenting accurate final answers. Significance: These errors were associated with misconceptions about variables and equality, limited conceptual understanding, and weak procedural fluency. In addition, instructional practices, including a strong emphasis on procedures and limited use of visual representations, contributed to these difficulties. This study highlights the importance of diagnostic error analysis and suggests the need for instructional approaches that integrate conceptual understanding, algebraic reasoning, and meaningful problem-solving experiences.